Importance of routine viral load monitoring: higher levels of resistance at ART failure in Uganda and Lesotho compared with Switzerland. (21st November 2018) - Bachmann, Nadine; von Braun, Amrei; Labhardt, Niklaus D; Kadelka, Claus; Günthard, Huldrych F; Sekaggya-Wiltshire, Christine; Castelnuovo, Barbara; Kambugu, Andrew; Lejone, Thabo I; Böni, Jürg; Yerly, Sabine; Perreau, Matthieu; et al.
Abstract: Objectives: Emerging resistance to antiretroviral drugs may jeopardize the achievements of improved access to ART. We compared the prevalence of different resistance mutations in HIV-infected adults with virological failure in a cohort with regular routine viral load (VL) monitoring (Switzerland) and cohorts with limited access to VL testing (Uganda and Lesotho). Methods: We considered individuals who had genotypic resistance testing (GRT) upon virological failure (≥1000 copies/mL) and were on ART consisting of at least one NNRTI and two NRTIs. From Lesotho, individuals with two subsequent VLs ≥1000 copies/mL despite enhanced adherence counselling ( n = 58) were included in the analysis. From Uganda, individuals with a single VL ≥1000 copies/mL ( n = 120) were included in the analysis. From the Swiss HIV Cohort Study (SHCS), a population without history of monotherapy or dual therapy with the first GRT upon virological failure ( n = 61) was selected. Results: We found that 50.8% of individuals in the SHCS, 72.5% in Uganda and 81.0% in Lesotho harboured HIV with high-level resistance to at least two drugs from their current regimen. Stanford resistance scores were higher in Uganda compared with Switzerland for all drugs used in first-line treatment except zidovudine and tenofovir ( P < 0.01) and higher in Lesotho compared with Uganda for all drugs used in first-line treatment except zidovudine ( P < 0.01). Conclusions: Frequent VL monitoring and possibly pretreatment GRT as done in the SHCS pays off by low levels of resistance even when treatment failure occurs. The high-level resistance patterns in Lesotho compared with Uganda could reflect a selection of strains with multiple resistance during enhanced adherence counselling.